Physics of Climate Change: Harmonic and exponential processes from in situ ocean time series observations show rapid asymmetric warming. - Matthews, J. Brian (JOURNAL OF ADVANCES IN PHYSICS, 2014)
Analyses of rare ocean timeseries in the top few meters show logarithmic and exponential processes control anthropogenic global warming (AGW) of which 93% is in the oceans. Processes result in asymmetric heat capture in the North and South tropical Pacific. A new Lagrangian paradigm established a global ocean surface freshwater and heat conveyor. Climate research wrongly assumed atmospheric pan-evaporation at sea as over land, a 10m well-mixed surface layer, and ignored that seawater density depends on both salinity and temperature. In situ observations show two different heat-capture and evaporation regimes exist dependent on surface temperature and salinity. The tropical North Pacific is temperature dominant, but other tropical oceans are salinity dependent. Incident solar radiation is cyclical and greenhouse gas (GHG) heat-capture is exponential and cumulative. The rate of GHG-caused climate change is disputed and not quantitatively evaluated. A target limit of total atmospheric temperature rise of <2°C is forecast from 30 to 100 years, or not at all. It is based on doubling of total carbon emissions from the long-term stable 280ppm to 560ppm. Here we show solar cycles became less significant compared to exponentially rising GHG heat capture after the 1957 solar maximum Keeling Point. The doubling time for exponential warming is 20 years at -0.030-0.037°Cyr-1. GHG warming of is now 1°C. At present rates, exponential increases add +1°C in 20yr, +2°C in 40yr, +4°C in 60yr, 8°C in 80yr above existing levels. Post-1957 carbon dioxide concentration GHG forcing is also doubling in 20yrs at 0.0268ppmyr-1. It rose from 1957-1976 by 17.1ppm, and from 1977-1996 by 34.4ppm. A further doubling by 68.4ppm would bring total emissions to 435ppm by 2017. It exceeded 400ppm in 2014. Carbon dioxide accounts for three quarters of the GHGs. Of the others, methane and HCFCs already may be out of control. Ocean surface temperature anomalies are close to the proposed +2°C limit. Century-long records in 5yr anomalies in the North Pacific show peaks of +1.6°C at the surface in 1995, and +1.3°C at 5m. North Atlantic peaks were +1.12°C in 2005 consistent Arctic freshwater fluxes. Central England temperature (CET) 5-yr peak air anomaly was +1.3°C in 2004 consistent with a rapid response in air due to low heat capacity. 2014 is a record year for temperatures and carbon dioxide total emissions. Pacific sub-surface water warmed faster than at the surface. The freshwater lid that thickened limits heat loss. The annual cycled heat increased by 3MJm-3 over 100yr at Isle of Man, by 1MJm-3 over 88yr at Scripps Pier surface, and by 4MJm-3 over 78yr at 5m. The post-1986 annual Arctic ice heat cycle decreased by -2,633MJm-3. Before 1986 tropical heat was offset against polar melt and runoff at Port Erin. After, exponentially decreasing Arctic ice reduced thickness from 1.9m-1.4m but surface area decreased more slowly than volume. This accounts for the observed increased polar ice formation surface layer at <4°C and <24.7° in Polar Seas. Process rate differences derive from the 3000x greater heat capacity of water to air (3.9x106: 1.3x103Jm-3°C-1), and the 1000x greater density (1023: 1.2 kgm-3). The top 10m operates on decadal timescales. Heat is trapped under a surface freshwater lid. Sub-surface heat penetration is on centennial and millennial timescales. It takes 250yr since the industrial revolution for two thirds of AGW to reach 300m. The flux of heat and freshwater through Bering Strait doubled from 2000-2007. It accounts for one third of surface layer meltwater fluxes into the Labrador Current at a rate of 0.85Sv. The Atlantic inflow of 8.5Sv accounts for the remainder with an Arctic residence time above the halocline of 2.5-6 years. This is consistent with the three and half years at the Isle of Man between the seasonal 1959 October high and the record 1963 February low. The Equatorial Undercurrent (EUC) compensates the land-locked Pacific surface layer bringing warm salty water under the Panama freshwater warm pool. We suggest the doubled warming of the North Pacific led to a quasi-permanent loop in the sub-polar jet stream. Warm air driven over Beringia displaces cold polar air to the North American mid-west. This resulted in continuous extreme weather over central North America in 2013-2014. In the southern hemisphere high evaporation resulted in record precipitation that temporarily reduced sealevels in 2012. Changed ocean ecological systems have been reported. The Pacific warming led to enhanced hurricane frequency from the Panama warm pool as well as super typhoons in the western North Pacific. North America now has hurricane seasons on both coasts and Hawaii, and extreme weather year-round. The warm tropical Gulf Stream/Columbus and Viking polar gyre boundary shifted northwards in the mid 1990s. It shows at Port Erin in a 1990s high seasonal salinity. After the millennium until records ceased in 2006, a seasonal freshwater layer was observed, consistent with a thickened freshwater lid over high salinity tropical water. Most long-term continuous records in the top 5m ceased in the mid 1980s. We suggest the ocean layer is warming exponentially and freshening. Global Ocean warming is known as the tragedy of the commons. Solutions include individual ownership and responsibility through, for example, managing fisheries by individual transferable quotas. The Zero Marginal Cost Society, the adopted goal of the UN and world leaders, requires a painful paradigm transition from a Newtonian to a Thermodynamic stable sustainable no-growth system. The option of population control cannot succeed in time. The EU leaders commitment to reduce GHG requires reduction of 8.9ppmyr-1 for the next 16 years to 2030. It is the only viable solution. However, it requires binding global commitments to a new paradigm conserving thermodynamic principles of maximized use of Earthâ€Ÿs natural resources. In economic terms this means narrowing the gap between rich and poor and deflation to stability of zero growth. Without immediate implementation, we suggest the exponential growth will continue, and may already be beyond control. Our work needs further experimental verification in the near-surface ocean on short space and timescales especially along meridional transects. The Isle of Man and Galapagos Islands, with both tropical and polar water, are ideal to establish constant monitoring of temperature, salinity, pH currents, and sealevel at 1, 2, 3, 5, 7, and 10m along with standard Met observations including pan evaporation and precipitation on purpose-build piers. Ocean-side measurements allow data to be collected efficiently with calibrated instruments if part of well-funded independent University level research. This way a new generation of young scientists well trained in classical physics can establish the scientific truth through experimental verification. This could proceed as part of a crash program to develop alternative natural energy resources based on geothermal heat exchange, pumped storage, tides and tidal currents, solar, winds and renewable carbon until nuclear fusion comes online as the ultimate solution.